Peningkatan keaktifan dan hasil belajar ipa melaluiModel snowball throwing pada siswa kelas ivDi sd muhammadiyah 10 tipesTahun 2015/2016 - Damayanti, Diana (2016)
This research aims to enhance: 1) the activity and 2) learning outcomes of science through models Snowball Throwing. This type of research is the Classroom Action Research (PTK) research design consists of four stages: planning, implementation, observation and reflection. Subjects in this study were teachers and students in the fourth grade students of SD Muhammadiyah 10 Tipes Year 2015/2016 . Data collection techniques in this study were interviews, observation, testing, and documentation. Data analysis technique used interactive . The results showed an increase in activity and learning outcomes of the fourth grade students of SD Muhammadiyah 10 Tipes. In the pre-cycle the average activity of students 41,38%, in first cycle 67.24%, and the second cycle 84.57%. While the percentage of enhancement of students learning outcome in pre-cycle 44,83%, in cycle I 75.86% and in the second cycle 86,94%. Based on the results of this study concluded that models Snowball Throwing can enhance the activity and learning outcomes of science in students grade IV in SDMuhammadiyah 10 Tipes